Incentives and complementarities of flexicurity - Alessio J. G. Brown; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2009)
This paper analyses how and to which degree the Danish flexicurity concept and its various elements achieve the renowned Danish miracle by evaluating their unemployment and inequality effects and their complementarities. We develop a microfounded model of searching workers and firms, calibrate it to Germany and perform the policy experiment of implementing the full Danish flexicurity set of policies (low employment protection, high unemployment benefits and workfare). Our results show that implementing the Danish flexicurity concept in Germany would reduce unemployment and earnings inequality substantially. Furthermore our analysis illustrates that the Danish flexicurity policies have some apparent complementarities in Germany - the reduction of unemployment effect is nearly 40% greater when the policies are implemented in conjunction than in isolation.
Keywords: J64; J65; E24; J22; J32; 330; Flexicurity; workfare; firing costs; employment; unemployment; Flexicurity; Arbeitsmarktflexibilisierung; Soziale Sicherung; Workfare; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Verteilungswirkung; Lohnstruktur; Dänemark; Deutschland